Kontribusi Komite Daerah Ekonomi dan Keuangan Syariah (KDEKS) terhadap Perkembangan Sektor Ekonomi Kota Bandar Lampung - Albab, Ulil; Sutopo, Heri; Algarini, Dona (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to investigate the contribution of the Regional Committee for Sharia Economics and Finance (KDEKS) to the development of the economic sector in Bandar Lampung City. The background of the study highlights the importance of sustainable economic growth in Indonesia, especially in the context of sharia economics as an effort to improve people's welfare. Although Indonesia has a Muslim majority population and has been active in developing sharia financial institutions, the existence of sharia finance is still relatively new and has a relatively small impact compared to the conventional financial sector. This study uses a qualitative descriptive approach, with data collection techniques including questionnaires, observations, and interviews. The research subjects involved the heads and members of KDEKS, while the research objects included regulations and policies, education and training, collaboration and synergy, infrastructure development, and promotion and marketing in the context of economic development in Bandar Lampung City. Data collection was carried out at the KDEKS office in Bandar Lampung City, with a research period of one month. Data were analyzed in stages, starting from data reduction, data presentation, to formulation or verification of conclusions. The results of the study show that KDEKS has a strategic role in the development of the sharia economic sector in Bandar Lampung City. Through this approach, researchers hope to provide a comprehensive picture of KDEKS's contribution to the city's economic development.